2000
DOI: 10.1002/1096-9101(2000)27:3<262::aid-lsm8>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

New technique for producing hybridoma by using laser radiation

Abstract: This new cell fusion method is characterized by production of hybridomas of target cells, lower cell toxicity, and a high rate of hybrid production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…As a result, the possibility of leaking small encapsulated molecules during the fusion decreases considerably. Previously, UV laser light was used to fuse individual cells, , and generally, multiple pulses had to be used in conjunction with poly(ethylene glycol), a chemical known to ease and, depending on the concentration, induce membrane fusion. In our experiments, a single UV pulse was sufficient to induce the fusion of liposomes suspended in a buffer solution without the addition of any membrane-destabilizing chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the possibility of leaking small encapsulated molecules during the fusion decreases considerably. Previously, UV laser light was used to fuse individual cells, , and generally, multiple pulses had to be used in conjunction with poly(ethylene glycol), a chemical known to ease and, depending on the concentration, induce membrane fusion. In our experiments, a single UV pulse was sufficient to induce the fusion of liposomes suspended in a buffer solution without the addition of any membrane-destabilizing chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…(20) It has also been reported that 5% PEG is sufficient to cause cell surface adhesion. (24) In conclusion, we have successfully proven each critical step in B-cell targeting on the basis of immunofluorescence. The application of this technology to in vitro immunization systems should bring about substantive progress for selective yielding of monoclonal antibodies in the short term.…”
Section: Discussionmentioning
confidence: 89%
“…The liposomes were brought into close contact using optical tweezers and made to fuse via a single high‐energy ultraviolet laser pulse, resulting in chemical reactions to occur between reactants in the different liposomes. In contrast to other studies which implement ultraviolet laser light to fuse individual cells, [164,165] their study was able to achieve this with a single pulse without the use of any membrane‐destabilizing chemicals. Shiomi et al [166] .…”
Section: Application Of Membrane Fusion Modelsmentioning
confidence: 85%